KONSEP AL-UZLAH PADA KISAH ASHABUL AL-KAHFI PENDEKATAN TAFSIR MAQASID AL-QUR’AN PANDANGAN IBN ĀSYŪR - Fatma Taufiq Hidayat; Laila Sari Mashury; Miftahul Fikria (Mozaic : Islam Nusantara, 2023)
Uzlah, as a concept known in general, is an activity to avoid, stay away from, or leave something away from the crowd. However, the meaning of al-Uzlah in the Qur’an in surah al-Kahf as a thematic theme has several meanings and purposes of the Qur’an, which is called Maqashid al-Qur'an from the expression of this meaning. This research describes the maqasid al-Qur'an of Ibn Ashur with the Maqasidi interpretation approach to the meaning of al-Uzlah in the story of Ashabul Kahfi in maintaining the creed. This study uses a type of library research (library research) with the Maqasidi interpretation approach method. The results of this study of the word al-Uzlah in surah al-Kahf verse 16 rest on three meanings and purposes, first: alienating or withdrawing from the crowd, second: escaping from the slander of disbelief and polytheism, and third: leaving for the sake of defending the faith and seek a place where worship is free. The variety of maqasid that can be directed is Aqedah as protecting religious interests rather than wealth and throne. Furthermore, from the side of morality and an ethic